The Effect of Grinding in Titanium Alloy Deformation. - Wójcik, Ryszard (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2013)
The machining of titanium alloys is relatively elaborate process which carries out large values of cutting forces and torques. For these reasons it is essential to impose specific requirements for tools, cooling system and lubrication. The present paper deals with examination of grinding process of titanium alloy with grinding wheels made of chromic electrocorundum and microcorundum. During investigation flat areas were grinded with the participation of minimum quantity lubrication and compressed air. On the basis of tests degree of the deformation and the parameter roughness Ra were examined.
Keywords: grinding; titanium alloys; minimum quantity lubrication (MQL); szlifowanie; stopy tytanu; minimalne smarowanie ilościowe